Performance Analysis of Restraint Grouting-Anchoring Lap Connection of Rebar in Prefabricated Shear Walls - Sun, Yuzhe; Bai, Guoliang (Tehnički vjesnik, 2023)
This study aims to obtain the key engineering parameters for the reliability performance of restraint grouting-anchoring lap connection of rebar, so as to achieve the promotion of prefabricated building. To study the performance of restraint grouting-anchoring lap connection of rebar in prefabricated shear walls, four parameters rebar diameter, lap length, bellows diameter and concrete strength were selected as the main subjects of the test. Specimens were prepared according to four important parameters. The test results show that the connection performance is reliable in the specimen of restraint grouting-anchoring lap connection of rebar for pre-drilled bellows. Through theoretical analysis, a force model was proposed to provide a quantitative analysis method for the theoretical calculation of the mechanical properties of restraint grouting-anchoring lap connection of rebar. As the diameter of the rebar increases, the spread of concrete stresses in the specimens becomes more pronounced; as the diameter of the rebar increases, the spread of concrete stresses in the specimens becomes more pronounced; the shorter the lap length, the higher the bond stress between the rebar and the concrete interface in the specimen, the damage of the specimen is from mild to severe; as the strength of the concrete increases, a larger diameter of rebar and a shorter lap length are required to achieve the same damage pattern in the specimen.